THE LANGUAGE REPRESENTATION OF SPATIAL ORIENTATION IN SPANISH - VALENTINA Korneva (Ибероамериканские тетради, 2016)
The article specifies the concept of spatial orientation and the potentials of the construction nombre sus-tantivo + adverbio are identified to determine the position of the human body and the body of an animal and an inanimate object in Spanish as well. It describes the functional capacity of the construction and the features of its representation at the lexical, morphological and syntactic levels